From military putsch to civilian government: appropriate responses by international actors - Kai Striebinger (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The trend for military putsches continued in 2015, with no end yet in sight. After the unsuccessful attempt in Burundi, the military in Burkina Faso once more seized power, albeit for a short duration. Putsches remain a widespread means of precipitating a change in government. Although the absolute global figure has decreased, Coups d'Etat remain particularly common in West Africa. Of 69 changes in government in the region between 1990 and 2014, 33 were elicited via elections and 18 via military putsches. International actors usually react to military putsches with two standard responses. Firstly, they demand that the putschists cede power to a civilian government. The African Union (AU) and the Economic Community of West African States (ECOWAS) are just two organisations which have formally declared, in legally binding documents, that a junta regime may not remain in power and that the next government must be appointed via elections. Secondly, several states and organisations including the USA and the AU have decided to impose sanctions automatically. This double response, consisting in the goal formulation of the swiftest possible transition to a civilian government and sanctions, creates a good basis for international actors to promote sustainable democratic structures. If democracy promotion is to be effective, however, three questions must be answered prior to any attempts in this area: What is the military's attitude towards democratic order? In the event that the putsch is an attempt to destabilise democratic order (as was recently the case in Burkina Faso), a hard-line policy against the putschists is appropriate. However, if the military is overthrowing an autocratic leadership, it may well prove a useful partner. What are the most pressing problems within the country's political system? International actors may be well advised to focus on military withdrawal in the event that a civilian government constitutes a sine qua non for democracy. However, this alone is not sufficient. Coups d'Etat are frequently an expression of deep-set structural problems. As a result, international actors should broaden their focus and address the root causes of the putsch. It may be expedient to combine steps towards reconciliation between political parties and security sector or judicial reforms with the demand for a civilian government. Which actions are appropriate in order to achieve these more broadly defined objectives? The suspension of cooperation may be a suitable means to penalise junta regimes. However, these measures should be complemented by other strategies. Restricting action to sanctions constricts scope for action unnecessarily. Military force, positive and negative, material and immaterial incentives as well as long-term persuasion efforts can, under specific conditions, complement traditional sanctions. The ultimate degree of success enjoyed by such measures depends heavily on the level of consensus reached by international actors and their legitimacy in the eyes of the addressees.
Keywords: 330; Governance; Demokratie und Autokratie